Dialogue on grief and consolation - O'Connell, Terence Lawlor. (Value Inquiry Book Series, 2009)
Have you lost a loved one? The loss can be inestimable, the grief excruciating. What helped you? Did someone say something comforting? Did someone offer a consolation, which you resented? Have you ever tried to comfort someone with a terminal illness or one who has lost a loved one? Knowing how to help or what to say that is not trite, insincere, or superficial can be difficult. The point of view of a grieving person is quite different from that of those who wish to offer comfort. In a multicultural society such as ours, anticipating the beliefs of the grieving person can be even more difficult. This book explores the perspective of a grieving person. It considers the merits and potential harm of alternative comfort strategies. As a philosophical analysis of grief, it emphasizes an understanding of the beliefs that underlie grief and the usefulness or dangers of emotions. Because grief is so complex and sensitive, a narrow approach runs the risk of alienating the grieving person. The ideas in this book are expressed in a dialogue among three characters. Their discussion is broad and fundamental. Starting from the familiar consolation, "She's no longer suffering" and the grieving person's resentment toward the expression, the three friends articulate the value of life and the evils of death. Their discussion enriches their understanding of grief. Many consolations offered to mourners are poor arguments. Even the better ones do their work best in the context of a greater understanding of grief.